PERANCANGAN SISTEM PEMESANAN MAKANAN KEDAI HDHT BERBASIS WEB - Ramadhan; Iqbal Febtien (Shofanah Media Berkah, 2023)
One of the problems faced by HDHT shops is the food ordering system which still uses the manual method. When customers want to order food, they have to go back and forth to the cashier which is on the first floor. This often causes long lines and inconveniences customers who have to queue to order food. In addition, the order recording system still uses manuals, which are prone to errors and difficult to track. Another problem is the payment system which is also done manually. Customers must face directly to a table for food ordering and payment, and to make payments customers often have to queue in long queues. To overcome this problem, a change is needed in the HDHT shop food ordering system. The design and implementation of a web-based food ordering system is the right solution to increase efficiency, convenience and customer experience in ordering food. With a web-based ordering system, customers can order food viaplatform online without having to go back and forth to the cashier, reducing queue time and increasing service speed.